Irreversibility distribution in heat transfer process of hollow paddle-shaft components. Issue 2 (15th June 2020) - Al-Kbodi, Basher Hassan; Rajeh, Taha; Zhang, Houlei
We present a second law-based investigation on the heat transfer performance of paddle-shaft components. Entropy generation rate distribution is obtained through numerical simulation. We show that the design with hollow paddles (HP) transfers more heat and causes larger entropy generation than that with solid paddles (SP). For HP, the solid domain produces much less entropy generation rate than the fluid domain and the material-solid interface. In the fluid domain, for SP, the pressure drop-induced irreversibility is negligible; for HP, it is important when the flow rate is large. For HP, near the flow holes, the local entropy generation rate is the largest, and near the fluid-paddle interface, it is less. In the centre regions of the fluid domain and the paddles, the local entropy generation rate is the least and approaches zero for both HP and SP. The work helps identify the dominant irreversibility and select proper designs in practice.